Pengujian Trade-Off Theory: Apakah Perusahaan di Indonesia Melakukan Optimalisasi Hutang? - misbach fuady (EBBANK, 2014)
This study examined the role of the trade-off theory (TOT) in determining the capital structure of public companies in Indonesia. Test material using financial statement data of public companies listed on the Indonesia Stock Exchange (IDX) in the period from 2002 to 2011, and meets the requirements for selected using purposive sampling method.Testing the trade-off theory uses a dynamic model that is partial terget adjustment model on panel data that has met the requirements of the classical assumptions.Research conducted shows that the actual debt adjustment to the target debt at a rate of 42.61% per year. This suggests that public companies in Indonesia shows the debt optimizing behavior by adjusting the actual debt to the target optimal debt in accordance with the concept of dynamic capital structure based on the trade-off theory.